Treatment of Resistant Hypertension in Real Clinical Settings - A. S. Maltseva; A. E. Tsygankova; M. A. Gabitova; A. V. Rodionov; V. V. Fomin (Столичная издательская компания, 2021)
Background. Current guidelines describe in detail the approaches to the management of patients with resistant hypertension, however, in real clinical settings the number of non-rational and ineffective combinations of antihypertensive drugs used remains high.Aim. To analyze the distribution of different combinations of antihypertensive drugs for the treatment of resistant hypertension and to estimate the proportion of non-rational combinations.Methods. The retrospective analysis includes 117 outpatients with resistant hypertension. Resistant hypertension was defined as blood pressure that remains above goal despite concurrent use of three antihypertensive agents of different classes. Exclusion criteria was secondary hypertension. We defined rational combination as the standard combination (renin-angiotensin system [RAS] blocker + calcium-channel blocker [CCB] + diuretic) plus one of the group of reserve drugs (mineralocorticoid receptors antagonist [MRA], beta-blocker, alpha-blocker, agonist of imidazoline receptors [AIR]). Non-rational were considered combinations in which reserve drugs were used before the appointment of a triple combination of first-line drugs. Moreover, in a subgroup of non-rational therapy, situations were identified where such a combination was justified.Results. The proportion of rational combinations was 58.9%, reasonably non-rational - 15.5%, unreasonably non-rational - 25.6%. Unreasonably non-rational combinations are distributed as follows: non-appointment of CCB - 12%, non-appointment of RAS-blockers - 8%, non-appointment of diuretics - 6%, use of RAS-blockers for hyperkalemia - 6%, administration of MRA without non-potassium-sparing diuretics - 5%, double blockade of RAS - 3%, other combinations - 7%. In addition to first-line drugs, beta-blockers (93.2%), loop diuretics (22.2%), AIR (21.4) were the most prescribable, while the proportion of MRA is only 15.4% of the entire sample.Limitation: some patient's characteristics could be missed in case histories and some of the combinations could be falsely recognized as malpractice since the analysis was conducted retrospectively.Conclusion. The proportion of the non-rational combinations for the treatment of resistant hypertension is high. Among the drugs of the reserve, the frequent use of beta-blockers and moxonidine and the inadequate administration of spironolactone are noteworthy. The problem of treatment strategy choice remains relevant in real clinical practice.